The Effectiveness of the Two Stay Two Stray (TSTS) Cooperative Learning Model Compared to the Jigsaw Type on Students' Science Learning Outcomes - Siti Nur Faiqoh; Sri Sami Asih (Postgraduate, University of Mataram, 2025)
The mismatch of models and objectives causes students' learning outcomes to vary. This study aims to determine the effectiveness of the Two Stay Two Stray (TSTS) cooperative learning model compared to the Jigsaw type in improving the learning outcomes of science students on the human digestive system material for class V SDIT Mutiara Hati Rembang. This study uses an experimental research type with a quasi-experimental research design in the form of Non-Equivalent Control Group Design. The sample in this study amounted to 54 students. The sampling technique used purposive sampling. Class VB as the control class and class VA as the experimental class. The data collection technique used a test technique in the form of pretest and posttest questions; non-test techniques in the form of interviews, observations, and documentation. The data analysis technique consists of initial data analysis in the form of normality tests and homogeneity tests and final data analysis in the form of t-tests and N-Gain tests. Based on the t-test, the sig. value is 0.013 (<0.05) meaning that Ho is rejected and Ha is accepted. So, there is a significant difference in the effectiveness of the application of the TSTS and Jigsaw learning models on the learning outcomes of science students for class V SDIT Mutiara Hati Rembang. Furthermore, based on the results of the N-Gain test, the control class was 0.46 and the experimental class was 0.56. In conclusion, the TSTS learning model is more effective than Jigsaw on social science learning outcomes